Effect of the temperature on the TMOS sono-hydrolysis and a study of the structure of the resulting aged sonogels - Vollet, D. R.; Donatti, D. A.; Ruiz, A. I.; Maceti, H. (Elsevier B.V., 2003)
The effect of temperature on the oxalic acid catalyzed sono-hydrolysis of tetramethoxysilane (TMOS) was studied by means of a heat flux calorimetric method. The activation energy of the process was measured as (24.5 +/- 0.8) kJ/mol in the temperature range between 10 and 50 degreesC. The structural characteristics of the resulting sonogels, after long period of aging in saturated conditions, were studied by means of small angle X-ray scattering. The structure can be described as formed by similar to2.7 nm mean size mass fractal-like aggregates (clusters) of primary silica particles of similar to0.3 nm mean size, all imbibed in a liquid phase. The average mass fractal dimension of the clusters was found to be 2.58. The primary particle density was estimated as 2.23 g/cm(3), in good agreement with the value frequently quoted for fused silica. The volume fraction of the clusters, in the saturated sonogels was estimated as about 28%. The moment in which the meniscus of the liquid phase penetrates into the clusters under rapid evaporation process has been detected by an inflection in the first derivative of the curve of weight loss in a simple thermogravimetric test. (C) 2003 Elsevier B.V. All rights reserved.